Enhancing College Students' Visual Literacy through Multimodal Analysis of Advertisements - Daman Huri; Yeti Mulyati; Vismaya S. Damaianti; Andoyo Sastromihardjo (Journal of General Education and Humanities, 2025)
Visualization in various aspects requires students to understand the meaning clearly, particularly through the skill of visual perception. This article examines how students' visual perception skills are applied in interpreting advertisements. The research method employed is a descriptive qualitative approach with multimodal analysis (linguistics, visual, audio, gestural, and spatial) to uncover the meanings behind advertisements. The respondents involved in this study are students from two universities in Indonesia. The results indicate that students tend to engage more with digital-based advertisements than non-digital ones, with a clear preference for video ads over static images. Additionally, Indonesian students successfully applied multimodal analyses to various types of advertisements. These findings have practical implications for educational practices, especially in enhancing visual literacy and developing critical skills for understanding and creating media. The significance of visual literacy in global educational contexts is highlighted, providing insight into its potential applications in curriculum development and advertising literacy.